Disparity in clinical outcomes between pure and combined pulmonary large-cell neuroendocrine carcinoma: A multi-center retrospective study. (January 2020) - Zhang, Jia-Tao; Li, Ye; Yan, Li-Xu; Zhu, Zheng-Fei; Dong, Xiao-Rong; Chu, Qian; Wu, Lin; Zhang, Hong-Mei; Xu, Chun-Wei; Lin, Gen; Yu, Zong-Yang; Hu, Jie; et al.
Highlights: Syn, CgA and CD56 were related to the prognosis of LCNEC. Adenocarcinoma was the most common combined components for LCNEC. SCLC chemotherapy regimen is a more effective choice for LCNEC. Overall survival of combined LCNEC tended to be shorter than pure LCNEC. Abstract: Objectives: The 2015 World Health Organization classification defines pulmonary large-cell neuroendocrine carcinoma (LCNEC) as a high-grade neuroendocrine carcinoma. However, the clinical characteristics and prognostic factors of pure LCNEC and combined LCNEC remain unclear. Hence, we performed a multi-center retrospective study to compare the clinical outcomes of pure versus combined LCNEC. Materials and methods: Data from 381 patients with pulmonary LCNEC admitted to 17 Chinese institutes between 2009 and 2016 were collected retrospectively. Clinical characteristics and prognosis were analyzed among patients receiving adjuvant (adjuvant group; n = 56) and first-line (first-line group; n = 146) chemotherapy, as well as among patients receiving small cell lung cancer (SCLC) and non-SCLC (NSCLC) chemotherapy regimens. The Kaplan-Meier method and multivariable Cox regression were used to identify clinicopathological variables that might influence patient outcomes. Results: Expression levels of neuroendocrine markers (synaptophysin, chromogranin-A, CD56) were associated with patients' prognosis in the total study cohort. In the adjuvant group, median disease-free survival was non-significantly longer for SCLC-based regimens than for NSCLC-based regimens (P = 0.112). In the first-line group, median progression-free survival was significantly longer for SCLC-based regimens than for NSCLC-based regimens (11.5 vs. 7.2 months, P = 0.003). Among patients with combined LCNEC, adenocarcinoma was the most common combined component, accounting for 70.0 % of cases. Additionally, median overall survival was non-significantly shorter for combined LCNEC than for pure LCNEC (P = 0.083). Conclusion: The SCLC regimen is a more effective choice, as either first-line or adjuvant chemotherapy, when compared to the NSCLC regimen for LCNEC treatment. Further studies are needed to clarify the survival differences between patients with pure-, and combined LCNEC.